The Effect of Blood Flow Restriction Exercise on Angiogenesis-Related Factors in Skeletal Muscle Among Healthy Adults: A Systematic Review and Meta-Analysis - Li, Shuoqi; Li, Shiming; Wang, Lifeng; Quan, Helong; Yu, Wenbing; Li, Ting; Li, Wei (Frontiers in Physiology, 2022)
Background. Blood flow restriction (BFR) exercise may be a potential exercise program to promote angiogenesis. This review aims to compare the effects of exercise with and without BFR on angiogenesis-related factors in skeletal muscle among healthy adults. Methodology. Searches were made in Web of Science, Scopus, PubMed, and EBSCO databases from January 2001 to June 2021. Studies were screened, quality was evaluated, and data were extracted. The review protocol was registered at PROSPERO (PROSPERO registration number: CRD42021261367). Standardized mean differences (SMD) of vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor 2 (VEGFR-2), hypoxia inducible factor 1α (HIF-1α), peroxisome proliferator-activated receptorγcoactivator-1α (PGC-1α) and endothelial nitric oxide synthase (eNOS) were analysed using Revman 5.4 software with a 95% confidence interval (95% CI). Results. Ten studies fulfilled the inclusion criteria with a total of 77 participants for BFR group or CON group. BFR exercise elicits greater release of VEGF (heterogeneity test, P = 0.09, I2 = 44%; SMD, 0.93 [0.38, 1.48]), VEGFR-2 (heterogeneity test, P = 0.81, I2 = 0%; SMD, 0.64 [0.08, 1.21]), HIF-1α (heterogeneity test, P = 0.67, I2 = 0%; SMD, 0.43 [0.03, 0.82]), PGC-1α (heterogeneity test, P = 0.02, I2 = 54%; SMD, 0.74 [0.21, 1.28]) and eNOS (heterogeneity test, P = 0.88, I2 = 0%; SMD, 0.60 [0.04, 1.17]) than non-BFR exercise. In the sub-group analysis, resistance exercise with BFR elicits greater release of VEGF (heterogeneity test, P = 0.36, I2 = 6%; SMD, 1.66 [0.97,2.35]) and HIF-1α (heterogeneity test, P = 0.56, I2 = 0%; SMD, 0.51 [0.01,1.02]) mRNA than aerobic exercise with BFR. Conclusions. Exercise with BFR elicited more angiogenesis-related factors mRNA expression than exercise without BFR, but not VEGF and PGC-1α protein expression. Therefore, BFR training may be a potential training program to improve vascular function.